Attitudinal aspects of early EFL learning - Lopriore, L. (Array, 2011)
Considerable research in early language learning has been done to date in second language (L2) contexts with bilingual learners or immersion students (e.g. Harley & Hart, 1997). However, an increasing number of studies are now appearing that are carried out in foreign language (FL) contexts. This seems to be a lucky coincidence because some highly significant characteristics impinging on the language learning process distinguish the two contexts (e.g. amount of exposure to the target language, quality of teaching, teacher charactetristics etc.), as pointed out by Nikolov & Mihaljević Djigunović (2006). Since early FL programmes have mushroomed worldwide in the last decade or so, there have appeared a number of comparative studies into the process of language learning by young FL learners, as well as into the process of teaching young learners (see, for example, Edelenbos, Johnstone & Kubanek, 2007 ; Mihaljević Djigunović, Nikolov & Ottó, 2008). In this study we focused on three aims. Firstly, we were interested in finding out about the initial attitudes of young beginners of English as a foreign language (EFL). Secondly, we wanted to see how these initial attitudes developed from grade 1 to grade 2. Thirdly, we tried to investigate the relationship of attitudes to other aspects of early learning of EFL, such as language behaviour during EFL classes and learning achievement.